2020
DOI: 10.22541/au.159646771.17059809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speckle Tracking Echocardiography Can Predict Subclinical Myocardial Involvement in Patients with Sarcoidosis: A Meta-Analysis

Abstract: Background This meta-analysis aims to evaluate the utility of speckle tracking echocardiography (STE) as a tool to evaluate for cardiac sarcoidosis (CS) early in its course. Electrocardiography and echocardiography have limited sensitivity in this role, while advanced imaging modalities such as cardiac magnetic resonance (CMR) and 18F-Fluorodeoxyglucose-Positron Emission Tomography (FDG-PET) are limited by cost and availability. Methods We compiled English language articles that reported left ventricular globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…TTE has been thought to have low sensitivity and specificity in diagnosing CS when compared with CMR and PET‐CT, 16 although TTE has advantage in terms of availability, portability, and cost‐effectiveness, but still provides valuable clues for the diagnosis 15 . The advent of STE allows more precise evaluation of the myocardial characteristics and function in many types of cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTE has been thought to have low sensitivity and specificity in diagnosing CS when compared with CMR and PET‐CT, 16 although TTE has advantage in terms of availability, portability, and cost‐effectiveness, but still provides valuable clues for the diagnosis 15 . The advent of STE allows more precise evaluation of the myocardial characteristics and function in many types of cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Newer echocardiographic parameters on myocardial mechanics such as strain may be useful for detecting dysfunctional myocardium even in the absence of apparent basal thinning. Studies demonstrated that among extra‐cardiac CS patients, global longitudinal strain (GLS) was reduced compared with normal controls, 14,15 with the reduction of strain prominent over the basal segments 14 …”
Section: Case Reportmentioning
confidence: 99%
“…Fread et al reported that LAGLS of ≤ 31.2% was associated with worse outcomes in patients with heart failure with preserved ejection fraction 27 . Regarding GLS in CS, a few studies reported the usefulness of 2D-STE for assessing LV function to predict the prognosis in sarcoidosis [28][29][30] . Cristina et al reported that reduced LVGLS and RVGLS were correlated with adverse cardiac events 30 .…”
Section: Gls Using 2d-stementioning
confidence: 99%
“…In addition, a meta-analysis performed by Barssoum K. et al, comprising 9 studies and 967 subjects, proved that both LV GLS and global circumferential strain are substantially lower in extracardiac sarcoidosis subjects and no clinical evidence of cardiac involvement and that the degree of LV GLS impairment correlates with the occurrence of major cardiac events [ 62 ]. Additionally, the circumferential strain has proved to be an indicator of fibrosis burden in subjects with extracardiac sarcoidosis.…”
Section: Advanced Echocardiographic Techniquesmentioning
confidence: 99%